Transmission Network Expansion Planning Considering Multiple Generation Scenarios - Escobar, A. H. (2008)
This paper presents a mathematical model and a methodology to solve a transmission network expansion planning problem considering open access. The methodology rinds the optimal transmission network expansion plan that allows the power system to operate adequately in an environment with multiples generation scenarios. The model presented is solved using a specialized genetic algorithm. The methodology is tested in a system from the literature.